2000
DOI: 10.4141/p99-051
|View full text |Cite
|
Sign up to set email alerts
|

Bloat in cattle grazing alfalfa cultivars selected for a low initial rate of digestion: A review

Abstract: . 2000. Bloat in cattle grazing alfalfa cultivars selected for a low initial rate of digestion: A review. Can. J. Plant. Sci. 80: 493-502. The occurrence of frothy bloat limits the practice of alfalfa grazing in spite of the availability of strains bred specifically for pasture. Bloat is a chronic condition, endemic to cattle. Prophylactics and management techniques are available to reduce its incidence but they are expensive, difficult to administer, conflict with traditional grazing management regimens and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 61 publications
0
35
0
3
Order By: Relevance
“…Legumes that contain condensed tannins (CT) such as sainfoin and birdsfoot trefoil ( Lotus corniculatus L.) do not cause bloat in ruminants (Berg et al, 2000). The CT bind to proteins through hydrophobic and hydrogen bonding in a pH‐dependent/reversible manner (Min et al, 2003), reducing the formation of stable foam and the incidence of bloat in ruminants (Li et al, 1996; McMahon et al, 1999).…”
mentioning
confidence: 99%
“…Legumes that contain condensed tannins (CT) such as sainfoin and birdsfoot trefoil ( Lotus corniculatus L.) do not cause bloat in ruminants (Berg et al, 2000). The CT bind to proteins through hydrophobic and hydrogen bonding in a pH‐dependent/reversible manner (Min et al, 2003), reducing the formation of stable foam and the incidence of bloat in ruminants (Li et al, 1996; McMahon et al, 1999).…”
mentioning
confidence: 99%
“…Low IRD selections were tested in grazing trials at Lethbridge and Kamloops. The resulting new alfalfa cultivar (AC Grazeland) reduced the incidence of bloat by an average of 56% compared with the control cultivar Beaver (Berg et al 2000). As well, these initial studies suggested that the severity of bloat was reduced as indicated by the reduction in multiple distensions of the rumen with AC Grazeland .…”
Section: Ac Grazelandmentioning
confidence: 90%
“…A breeding program had selected AC Grazeland for bloat reduction on the basis of low initial rates of digestion in the rumen. Compared with its parental cultivar, Beaver, it reduced bloat by 56% (Berg et al 2000). Further work demonstrated that the bloat reduction observed with AC Grazeland was a result of the selected cultivar having a faster rate of maturity.…”
mentioning
confidence: 87%